Artificial Engine Sound Synthesis Method for Modification of the Acoustic Characteristics of Electric Vehicles - Dongki Min; Buhm Park; Junhong Park (Shock and Vibration)
Sound radiation from electric motor-driven vehicles is negligibly small compared to sound radiation from internal combustion engine automobiles. When running on a local road, an artificial sound is required as a warning signal for the safety of pedestrians. In this study, an engine sound was synthesized by combining artificial mechanical and combustion sounds. The mechanical sounds were made by summing harmonic components representing sounds from rotating engine cranks. The harmonic components, including not only magnitude but also phase due to frequency, were obtained by the numerical integration method. The combustion noise was simulated by random sounds with similar spectral characteristics to the measured value and its amplitude was synchronized by the rotating speed. Important parameters essential for the synthesized sound to be evaluated as radiation from actual engines were proposed. This approach enabled playing of sounds for arbitrary engines. The synthesized engine sounds were evaluated for recognizability of vehicle approach and sound impression through auditory experiments.